The Impact of the Environmental Situation on the Landscapes of the Caspian Sea Coast's Azerbaijan - Humbatova Shafiqa; Abbasova Gunay; Humbatov Mahmud (BIO Web of Conferences)
Coastal transformation as a result of hydrodynamic factors and sea level changes has a significant impact on ecosystems, economic infrastructure and coastal population. [3] Rapid changes in the Caspian Sea level have created unstable conditions for the coastal environment since the 20th century. The aim of this study is to study the impact of pollution on the ecosystem, infrastructure of adjacent areas, natural tourism resources, people, landscape transformations of the Azerbaijani Caspian Sea coast, as well as to assess the magnitude of coastline displacement and morphological changes.